Telitacicept for refractory AChR-positive generalized myasthenia gravis: a retrospective real-world study - Rong, Xi; Sun, Xupeng; Wang, Li; Qu, Meijie; Jiang, Liwei; Liu, Min (Frontiers in Immunology, 2026)
Background and aimsTreating refractory acetylcholine receptor-positive generalized myasthenia gravis (AChR+ gMG) remains challenging, especially for patients requiring long-term immunosuppressive therapy. Current treatments often lack specificity and pose significant long-term risks, underscoring the need for alternatives. Telitacicept, a novel dual inhibitor of B lymphocyte stimulator (BLyS) and proliferation-inducing ligand (APRIL), offers a promising targeted therapeutic approach. This study aimed to evaluate the efficacy and safety of telitacicept in the treatment of refractory AChR+ generalized myasthenia gravis.MethodsThis retrospective study included 42 patients with refractory AChR+ gMG who received telitacicept. The primary outcomes assessed were changes from baseline in Quantitative Myasthenia Gravis (QMG) scores, analyzed using mixed-effects models. Secondary outcomes comprised cumulative response rates, reductions in concomitant immunosuppressive medications, and safety events.ResultsA total of 42 refractory MG patients with MGFA class II–IV were enrolled. Significant improvements were observed in the QMG total score (least-squares [LS] mean change at month 5: -2.24, 95% CI -3.34 to -1.15, p<0.001), with sustained benefits across ocular, limb, and bulbar areas. Cumulative response rates reached 69.9% for MGFA-PIS and 73.8% for QMG improvement (≥3-point reduction) by 6 months. Notable decreases in prednisone (LS mean -10.17 mg/day, p<0.001) and immunosuppressant use were also seen. The therapy demonstrated a promising safety profile.ConclusionsTelitacicept demonstrated significant efficacy in refractory AChR+ gMG and may reduce dependence on traditional immunosuppressants. These real-world findings support its use as a valuable treatment choice for this challenging patient group.